2021
DOI: 10.3389/fmed.2021.774946
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics Analysis, Clinical Outcome and Risk Factors for Fungal Peritonitis in Peritoneal Dialysis Patients: A 10-Year Case-Control Study

Abstract: Background: Fungal peritonitis (FP) is a rare but severe complication that can appear in patients receiving peritoneal dialysis (PD). This study aimed to investigate the incidence rate and clinical characteristics of FP, evaluate clinical outcomes between FP and bacterial peritonitis (BP) patients on PD, and especially estimate the risk factors for FP outbreak.Methods: All episodes of FP diagnosed in our hospital from January 1, 2011, to December 31, 2020, were reviewed in this single-center study. FP cases we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…Although the proportion of mycobacterial PDAP among the total PDAP cases decreased, the proportion of fungal PDAP and polymicrobial PDAP among the total PDAP cases increased in our study area. Therefore, to prevent fungal or polymicrobial infections, more attention should be paid to susceptible patients, such as those with gastrointestinal dysfunction, constipation, recent bacterial PDAP and/or antibiotic therapy, advanced old age and diabetes [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…Although the proportion of mycobacterial PDAP among the total PDAP cases decreased, the proportion of fungal PDAP and polymicrobial PDAP among the total PDAP cases increased in our study area. Therefore, to prevent fungal or polymicrobial infections, more attention should be paid to susceptible patients, such as those with gastrointestinal dysfunction, constipation, recent bacterial PDAP and/or antibiotic therapy, advanced old age and diabetes [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…To avoid missing important risk factors in the multivariate logistic regression analysis, the p -value for significance was relaxed to 0.2. In statistical language, a p -value <0.2 is acceptable ( 22 ). Technique survival rates were assessed using the Kaplan–Meier method and the differences between the two groups were compared by the log-rank test.…”
Section: Methodsmentioning
confidence: 99%
“…Recommendations are to consider clinical response aimed at balancing the risk of prolonged antibiotic therapy. It should be noted that many observational studies in patients with fungal peritonitis confirmed the risk factor of antibiotic use within 1 month of the onset of peritonitis [8,27,28]. Because there is insufficient data to support a fixed biweekly treatment protocol, it is considered reasonable to prescribe antibiotics for a period of 7-10 days (Figure 1), which is the time required to resolve an uncomplicated acute infection.…”
Section: Principles Of Management Of Peritoneal Dialysis Catheter-rel...mentioning
confidence: 99%